Osseointegration of zirconia and titanium implants in a rabbit tibiae model evaluated by microtomography, histomorphometry and fluorochrome labeling analyses. (17th October 2017) - Martins, R.; Cestari, T. M.; Arantes, R. V. N.; Santos, P. S.; Taga, R.; Carbonari, M. J.; Oliveira, R. C.
Abstract : Objectives: This study compares the osseointegration of machined‐zirconia implants containing yttria (M‐Y‐TZP) with machined (M‐Ti) and resorbable blast media (RBM‐Ti) titanium implants. Material and Methods: M‐Y‐TZP, M‐Ti and RBM‐Ti implants were randomly placed in rabbit tibiae. Fluorochrome bone labels (tetracycline, alizarin and calcein) were administered at different time periods. After 8 weeks, osseointegration was evaluated in terms of bone‐to‐implant contact (BIC), new bone area (nBA), remaining cortical bone area (rBA) and temporal quantification of fluorochromes, using micro‐CT and histomorphometric analyses. Results: RBM‐Ti implants showed higher resorption of the remaining cortical bone and bone formation (rBA = 36.9% and nBA = 38.8%) than M‐Y‐TZP implants (rBA = 48% and nBA = 26.5%). The BIC values showed no differences among the groups in the cortical region (mean = 52.2%) but in the medullary region, they were 0.45‐fold higher in the RBM‐Ti group (51.2%) than in the M‐Y‐TZP group (35.2%). In all groups, high incorporation of tetracycline was observed (2nd to 4th weeks), followed by alizarin (4th to 6th weeks) and calcein (6th to 8th weeks). In the cortical region, incorporation of tetracycline was similar between RBM‐Ti (49.8%) and M‐Y‐TZP (35.9%) implants, but higher than M‐Ti (28.2%) implants. Subsequently, alizarin and calcein were 1.1‐fold higher in RBM‐Ti implants than in the other implants. In the medullary region, no significant differences were observed for all fluorochromes. Conclusion: All implants favored bone formation and consequently promoted primary stability. Bone formation around the threads was faster in RBM‐Ti and M‐Y‐TZP implants than in M‐Ti implants, but limited bone remodeling with M‐Y‐TZP implants over time can have significant effects on secondary stability, suggesting caution for its use as an alternative substitute for titanium implants.